PENGARUH MODEL PROBING PROMTING BERBASIS KEARIFAN LOKAL TERHADAP SIKAP CINTA LINGKUNGAN PESERTA DIDIK KELAS IV - Ratnawati, Alfia; Yusuf, Yusuf; Prihastari, Ema Butsi (Elementary School Teacher and Education (PGSD), Faculty of Teacher Training and Education, 2019)
The purpose of this research was to study the attitude of environmental love of students in grade IV of SD Negeri Kauman No.27 Surakarta with an influence probing promting model based on local wisdom in the discussion of shapes in the Academic Year 2018/2019 . This research was quantitative research with the design of One Group Pretest-Posttest Design. The population of all grade IV students of Kauman State No.27 Surakarta in Academic Year 2018/2019 gathered 32 students with saturated sampling techniques. Data collection techniques were in this study through questionnaires, observation, interviews, and documentation. The data analysis technique used paired sample t-test. Based on the results of data analysis, the value of accounting is 3,869. While tcount is compared with t table with d.b = (N-1) = (32-1) at a significance level of 5% = 2,040 or obtained tcount (3,869)> ttable (2,041). So, it can be announced that